Identification of stable genotypes based on grain yield response over different environments in sorghum (Sorghum bicolor L. Moench) - Veldandi Saikiran1, D. Shivani1, S. Maheswaramma2, S. Ramesh4, K. Sujatha3, K. Sravanthi2, K. N Yamini5, B. V. Varaprasad1 and C. V. Sameer Kumar1* (Electronic Journal of Plant Breeding, 2022)
The genotype × environment (G × E) interaction has a significant impact on plant yield performance and is an important focus of researchers in developing stable varieties. This study aims to find stable, high yielding sorghum hybrids suited for a wide range of environmental conditions in Telangana. A total of 64 sorghum genotypes/hybrids were evaluated in three environments during Rabi 2020–2021 for adaptability and stability. The regression method of stability analysis was used to study grain yield adaptability and stability. Results revealed that, genotypes, environments, G × E interaction, and G × E (linear) all differed significantly. According to the findings, the highest yielding hybrid was SG-16 (2.78 kg/ plot). Based on the regression coefficient (bi) and deviation from regression (s2di) scores, the high yielding hybrids, viz., SG-26, SG-16, SG-3, SG-29, and SG-6, were found to be stable and adapted to a wide range of environments.